UPAYA MENINGKATKAN PENGETAHUAN DAMPAK SMARTPHONE TERHADAP PENDIDIKAN DAN KESEHATAN DI KELURAHAN PELAWI UTARA KECAMATAN BABALAN KABUPATEN LANGKAT - Selly Oktaria; Efrilia Efrilia; Dwi Fitri Pratiwi (Universitas Islam Sumatear Utara, 2022)
North Pelawi Village has the problem of not controlling elementary school children in using smartphones. Smartphone which is a smart phone whose existence is now important because its available features make it easier for users to carry out daily activities. With a smartphone, you can easily get information from all over the world. smartphones have both positive and negative impacts on education and health. Smartphones can cause addiction that has the same symptoms as addiction to other psychoactive substances. Cell phones or smartphones can emit microwaves in the form of radio waves. Microwaves can affect hormones and neurotransmitters. Smartphone addicts can cause withdrawal syndrome. This can have an impact on education. method used to prevent the impact of this Smartphone is Providing Education to Students in Elementary Schools in North Pelawi Village about the impact of Smartphones on Education and Health, and Provide education on how to wisely use Smartphones as Learning Media and as a result, students have understood the impacts that occur in education and in health, can know the benefits of smartphones as learning media and can hone their own potential.